Inovasi Sosial di Yogyakarta: Pengabdian Masyarakat dalam Membangun Harmoni Keagamaan - Fajri, Rahmat (Abdimas Indonesian Journal, 2023)
The aim of carrying out this service is to carry out social innovation in Yogyakarta in community service in building religious harmony. The community service initiative in Yogyakarta uses the ABCD approach to strengthen religious harmony by identifying and exploiting local potential, involving the community in training, cross-institutional collaboration, and implementing small programs. Through active participation and dissemination of results to stakeholders, this initiative aims to build mutual understanding and interfaith cooperation amidst the diversity of Yogyakarta society. The results of community service in Yogyakarta by identifying local potential, such as stories, religious figures, places of worship, festivals and traditions, as resources for building religious harmony. Next steps involve establishing working groups, training, and inter-agency collaboration to implement small programs with active community participation, evaluated periodically. Community participation in small group discussions is key in understanding religious needs and expectations, embracing diversity of views, and creating local solutions. Training and the formation of working groups succeeded in strengthening individual skills and the collective capacity of society, creating positive changes in both the short and long term. Dissemination of results through social media and community meetings ensures that inspiration and learning from this social innovation can reach communities in various regions.